Interaction between forming and joint quality of the friction-assisted clinching. Issue 1 (November 2020) - Li, Zhiyong; Wang, Zhiyong; Li, Yong; Han, Shanling
Abstract: In order to achieve the effective joining of aluminum and magnesium alloy sheets, a friction-assisted clinching is innovatively proposed to reduce material damage during the process and improve the joint quality. 2 mm thick Al5052 aluminum sheet and 2 mm thick AZ31 magnesium alloy sheet were selected as the research objects, the interaction between different forming parameters, i.e., die depth, rotational speed and rotation time, and the joint quality, i.e., the damage, neck and interlock were explored by DEFORM-3D. The influence of sheet temperature on damage and punch load is analysed, the rotational speed and rotation time have great influence on the forming joint, the die depth mainly affects the neck and interlock. Comparing the joint qualities under different forming parameter combinations, it is found that the joint quality is the best when the bottom die depth is 2.2 mm and the bottom punch is applied at 1000 rpm for 0.5 s. The research will provide a valuable reference for the realization of joining the aluminum and magnesium sheets.